MNC responses to international NGO activist campaigns: Evidence from Royal Dutch/Shell in apartheid South Africa - Minefee, Ishva; Bucheli, Marcelo (Journal of International Business Studies, 2021)
Multinational corporations (MNCs) operating in countries with a poor human rights record are often the target of nongovernmental organizations (NGOs) that argue that MNCs’ decisions to stay in those countries represents support of those repressive governments. Consequently, NGOs often develop global campaigns to pressure MNCs to divest from those countries. We study how MNCs respond to these pressures through the revelatory case of the global divestment campaign against Royal Dutch/Shell during the racist apartheid regime in South Africa in the 1980s. We combine archival-based historical research and visual rhetorical analysis, and find that Royal Dutch/Shell developed a strategy consisting of creating counter-narratives at three different levels for actors within the MNC that had different interests. First, the headquarters sought to avoid setting a precedent for future boycotts; second, the peripheral subsidiaries aimed to avoid having their reputation tarnished by what was happening in South Africa; and third, the focal subsidiary was fighting for its survival. Building from this case, we inductively offer a model to analyze MNC responses to global NGO activism and discuss implications for MNCs’ political activities, their role in the defense of human rights, and strategies of corporate social responsibility.